Obstetric and perinatal aspects of choosing folate containing medications for miscarriage treatment - N A Kurmacheva; O M Kharitonova; E V Verizhnikova (IP Berlin A.V., 2016)
Objective - to compare the pregnancy and the condition of full-term newborns of women with gene polymorphisms of folate cycle and a history of miscarriage, receiving metafolin containing complex and mega-doses of folic acid (FA). Materials and methods. A retrospective study of medical records of 114 patients (form number 025/a, 111/a, 113/y). Compare homocysteine levels, coagulation screening indicators, peculiarities of pregnancy, childbirth, newborn status, depending on the version of folate deficiency correction. Results. In the group of patients treated with metafoline containing vitamin and mineral complex (n=60) had significantly lower levels of homocysteine, fibrinogen, thrombinemia markers, the frequency of some obstetric and perinatal complications (in 1.5-3.9 times; p